PERANAN MEDIATOR DALAM PENYELESAIAN SENGKETA PEMBAGIAN WARIS POLIGAMI (STUDI AKTA PERDAMAIAN NOTARIS MEDIATOR NOMOR 40 TANGGAL 23 JUNI 2011) - NOVASELLA SAKINAH AS’AD (PREMISE LAW JURNAL, 2016)
Man possesses various needs in his life. To fulfil his needs in his interaction with the others, a regulation is required. Justice and legal certainty are one of the important needs in the society. Therefore, people make some legal regulations to be obeyed and will be upheld if there is an offense. Problems arisen in this thesis are how the mediator’s performance to solve the dispute out of court, how the solution mechanism of the dispute of sharing of polygamy inheritance carried out by the mediator, and how the mediator’s roles are to solve the dispute of sharing of  polygamy inheritance. The type of research of this thesis is a legal research using  the normative-juridical approach, namely a research which refers to the application of legal norms conducted in forms of doctrines and principles in legal science. Keywords: Mediator, Dispute Solution, Sharing of Inheritance